2008
DOI: 10.1167/iovs.08-2078
|View full text |Cite
|
Sign up to set email alerts
|

α2 Adrenergic Modulation of NMDA Receptor Function as a Major Mechanism of RGC Protection in Experimental Glaucoma and Retinal Excitotoxicity

Abstract: The results demonstrate alpha2 modulation of NMDA receptor function as an important mechanism for neuroprotection. These results suggest a new therapeutic approach based on neuromodulation, instead of direct inhibition, of the NMDA receptor for the treatment of glaucoma and other CNS disorders associated with NMDA receptor overactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 41 publications
1
103
0
5
Order By: Relevance
“…The N-methyl-D-aspartate (NMDA) receptors are highly permeable to Ca ++ ions, and an intracellular Ca ++ overload can lead to excitotoxicity and neuronal cell death. Dong and collaborators (2008) has shown that Brimonidine preserves RGCs by blocking NMDA receptors (31) . In addition, Brimonidine has been shown to up-regulate endogenous BDNF expression in RGCs, a potent neuroprotective factor that promotes RGC survival following optic nerve crush injury (32) .…”
Section: Discussionmentioning
confidence: 99%
“…The N-methyl-D-aspartate (NMDA) receptors are highly permeable to Ca ++ ions, and an intracellular Ca ++ overload can lead to excitotoxicity and neuronal cell death. Dong and collaborators (2008) has shown that Brimonidine preserves RGCs by blocking NMDA receptors (31) . In addition, Brimonidine has been shown to up-regulate endogenous BDNF expression in RGCs, a potent neuroprotective factor that promotes RGC survival following optic nerve crush injury (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Retinal ganglion cells express abundant NMDA receptors [106][107][108][109]. A number of studies demonstrated that ganglion cells are extremely vulnerable to exogenously applied NMDA, which inducesganglion cell degeneration.It has been also shown that NMDA receptor antagonists are neuroprotective in experimental glaucoma models [110][111][112][113][114][115][116][117].…”
Section: A Nmda Receptorsmentioning
confidence: 99%
“…The positive effect of Brimonidine on RGC survival, that includes a reduction in their soma size in a rat model of o c u l a r h y p e r t e n s i o n , i s b e l i e v e d t o b e m e diated through the attenuation of glutamate toxicity by inhibition of NMDA receptor function (Dong et al, 2008) and/or the upregulation of brain-derived neurotrophic factors (Hernandez et al, 2008). However, in a rat model of pressure-induced retinal ischemia, it was suggested that Brimonidine's neuroprotective effect is mediated via the inhibition of the apoptotic cascade, possibly through the induction of anti-apoptotic genes such as bcl-2 and bcl-x, as well as extracellular-signal regulated kinases (ERKs) and phosphatidylinositol-30 kinase/ protein kinase Akt pathways (Lai et al, 2002).While Brimonidine's effect on RGCs in isolated rat retinas, as well as in vivo in rat and rabbit glaucoma models was also shown to be mediated through the reduction of a2-adrenoceptor mediated reduction of intracellular cAMP (Dong et al, 2008). A clinical trial assessing the non-IOP-related effects of Brimonidine, demonstrated reduced visual field deterioration in comparison to 360° laser trabeculoplasty (Gandolfi et al, 2003) .…”
Section: Compounds With Multiple/novel Mechanisms Of Actionmentioning
confidence: 99%
“…As a result, energy compromised neurons cannot maintain ionic homeostasis and become depolarized. Modulation of the NMDA receptor has been constituted a major area of research in glaucoma neuroprotection (Dong et al, 2008;Guo et al, 2006). In vivo and in vitro studies have suggested that blocking both the NMDA and the non-NMDA receptors simultaneously offers optimal protection against ischemic neurodegeneration (Mosinger et al, 1991).…”
mentioning
confidence: 99%